2018
DOI: 10.1111/jbg.12372
|View full text |Cite
|
Sign up to set email alerts
|

Selecting for changes in average “parity curve” pattern of litter size in Large White pigs

Abstract: This study aimed to analyse genetic background of variation in reproductive performance between parities of a sow and to investigate selection strategies to change the “parity curve”. Total number born (TNB) recorded in Large White sows was provided by Topigs Norsvin. Analysis with basic (BM) and random regression (RRM) models was done in ASReml 4.1. The BM included only a fixed “parity curve”, while RRM included 3rd order polynomials for additive genetic and permanent sow effects. Parameters from RRM were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…The random regression model estimated them to be higher than 0.90, among which those between the first and second parities were the lowest in both breeds. A similar phenomenon has been observed in total number born (Sell‐Kubiak et al, ). Other studies have also reported that the genetic correlation of NBA between the first and second parities was slightly lower than those between other successive parities (e.g., David et al, ; Hanenberg et al, ; Lukovic et al, ).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The random regression model estimated them to be higher than 0.90, among which those between the first and second parities were the lowest in both breeds. A similar phenomenon has been observed in total number born (Sell‐Kubiak et al, ). Other studies have also reported that the genetic correlation of NBA between the first and second parities was slightly lower than those between other successive parities (e.g., David et al, ; Hanenberg et al, ; Lukovic et al, ).…”
Section: Resultssupporting
confidence: 82%
“…Estimated heritability using the random regression model was lower than that using repeatability animal model at only the second parity. On the other hand, Sell‐Kubiak et al () analyzed the records of total number born from the first to the tenth parities in Large White sows provided by Topigs Norsvin, using a repeatability animal model, a multiple‐trait model regarding all parities as different traits each other, and a random‐regression model. These models assumed the heterogenous residual variances, and the magnitude relation of the heritability estimates among the models were different depending on parity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last years, the methodology introduced by Rönnegård et al (2010) using double hierarchical generalized linear model (DHGLM) and individual residual variances was applied to estimate phenotypes for variability (Felleki, Lee, Lee, Gilmour, & Rönnegård, 2012; Mulder, Rönnegård, et al, 2013). In this approach, it is crucial to obtain the most accurate estimates of residuals, which could differ significantly depending on the model used (Sell‐Kubiak, Knol, & Mulder, 2019). Nevertheless, methods based on DHGLM require high computing power and due to their complexity are in general difficult to implement in breeding programmes.…”
Section: Introductionmentioning
confidence: 99%